Field reports form for submitting seasonal observations of Iowa birds, Carolyn J. Fischer, fall 1993 - Fischer, Carolyn J.et al (1993)
Fall report of birds found in northern Iowa contributed by Carolyn J. Fischer. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1993. Plustek - flatbed